Comparative Study of Water Chemical Quality in the Air Telang Protected Mangrove Forest During the West and East Monsoons - Dewi Rosanti; Indra Yustian; Sarno Sarno; Syaiful Eddy (Journal of Biotropical Research and Nature Technology, 2026)
A study on the differences in water chemical quality in the mangrove area of ​​the Air Telang Protection Forest during the western and eastern rainy seasons was conducted from October 2024 (eastern monsoon) to April 2025 (western monsoon). The aim was to compare the water chemical quality, namely BOD, COD, DO, and pH in the area during the western and eastern monsoons, which support aquatic biota that depend on mangrove forests as spawning, feeding, and nursery grounds. This study used a survey method, with sampling carried out at five stations in different vegetation zones, namely the emerging sand (station 1), Sonneratia zone (station 2), Avicennia zone (station 3), Nipah degraded zone (station 4), and Rhizophora zone (station 5). The parameters observed were BOD, COD, DO, and pH. Samples were taken 3 times at each station. Based on the discussion above, it can be concluded that water quality during the east monsoon is better than during the west monsoon, based on chemical parameters such as BOD, COD, DO, and pH. However, during the west monsoon, only pH is tolerable for aquatic biota. This can be used as a basis for environmental management around mangrove ecosystems for the conservation of aquatic biota, as part of silvofishery (aquaculture) development.